A brief review on therapeutic approaches for face and non-face recognition disorders: summarising recent clinical developments - Mondal, Ritwick; Deb, Shramana; Lahiri, Durjoy; Shome, Gourav; Saha, Somesh (International Journal of Research in Medical Sciences, 2022)
Face recognition is considered as an important phenomenon in our everyday life. In 19th century cognitive science got introduced with a new term ‘prosopagnosia’ (face recognition disorder) for the first time by Joachim Bodmer. The term is derived from Greek word prosopon (face) and gnosis (knowledge), and refers to a condition which was first observed as a consequence of brain lesions (acquired prosopagnosia). Initially it was believed that prosopagnosia results due to brain injury but later congenital or hereditary form of face recognition disorder was also reported. The therapeutic modalities of this rare disorder are still unclear but with the advancement of scientific understanding different diagnostic procedures as well as therapeutic strategies are developed. These treatment procedures impart an impactful result among the individuals suffering from this disorder. Here in this article, we reviewed about various treatment approaches of acquired prosopagnosia and development prosopagnosia.